AI product knowledge as moderator of trust and attitude in usage intention: a study of Indonesian postgraduates - Nanang Suryadi; Rizka Zulfikar; Yudhita Valen Prasarry; Muhammad Fajrul Islam F (Cogent Social Sciences, 2025)
This study examined the moderating effect of knowledge on artificial intelligence (AI) products in the relationship between trust, attitude, and intention to use technology among Indonesian postgraduate students. Using a quantitative approach with SEM-PLS on 260 respondents, the study’s novelty lies in exploring AI knowledge as a moderating variable, a topic not widely studied in AI usage intentions. Results show that trust and attitude positively affect intention to use AI, while AI product knowledge does not directly influence usage intention. However, AI knowledge moderates the relationship between attitude and intention but not between trust and intention. These findings suggest that technical knowledge can strengthen positive attitudes toward AI but is insufficient to significantly influence trust. The study contributes to AI adoption literature by integrating AI knowledge into the Theory of Planned Behavior (TPB) and Interpersonal Trust Theory (ITT), offering insights into the cognitive and emotional factors driving AI acceptance among students. Practically, it highlights the importance of transparency and user education in promoting AI adoption across sectors like education, healthcare, and e-commerce.